ANALYSIS OF CHLOROPHYLL-α AND SEA SURFACE TEMPERATURE DISTRIBUTION USING SATELITE IMAGE TO ESTIMATE OF FISHING ZONES FOR YELLOWFIN TUNA (Thunnus albacares) IN WEST SUMATERA PROVINCE WATERS - Arta, Fandi Handika; Mubarak, Mubarak; Nasution, Syafruddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
The potential of tuna in the waters of West Sumatra reaches 300,000 tons per year, and only 25% of its existing potential has been exploited. The existence of these fish can be determined by measuring the concentration of chlorophyll-α as an indicator of food sources in the waters and measuring sea surface temperature as an indicator of the fish environment, which can be done using remote sensing technology. This research was conducted from August 05 to September 29, 2022, using Aqua MODIS satellite imagery data. The results obtained during the study showed that the concentration of chlorophyll-α had an average of 2.01 mg/m3. The highest concentration occurred in the period 13-20 August 2022 with an average value of 3.17 mg/m3, and the lowest occurred in the period 06-13 September 2022 with an average value of 0.85 mg/m3. Sea surface temperature has a relatively similar value, which ranges from 29.5–30.8oC with an average of 30.5oC. Determination of the alleged fishing area for yellowfin tuna was carried out using the overlay technique by shading the area from chlorophyll-a criteria >0.1 mg/m3 with the sea surface temperature criteria of 29-30oC. The accuracy level of the yellowfin tuna fishing area estimation has an average accuracy of 28.7%. The highest accuracy value occurs from August 29 to September 05 2022, with a percentage of 69.8%, and the lowest occurs from August 13 to 20, 2022, with a rate of 3.9%.